Oxide ion/electronic polarizability, optical basicity and linear dielectric susceptibility of TeO2 - B2O3 - SiO2 glasses - Umar, Saad Aliyu; Mohamed Kamari, Halimah; Ibrahim, Gana Geidam; Alade, Ibrahim Olanrewaju; Abd Azis, Muhammad Noorazlan; El-Mallawany, Raouf A.H.; Hamza, Abdulkarim Muhammad; Nazrin, S. N.; Grema, Lawan U.; Otto, Muhammed Sani (Elsevier, 2021)
A system of bio-silica borotellurite glasses was fabricated based on the chemical formula [(TeO2)0.7 (B2O3)0.3]1-x (SiO2)x with x = 0.1, 0.2, 0.3, and 0.4 using the melt-quenching technique using silica (98.548% SiO2, from rice husk), TeO2 (Alfar Aeser, 99.9%) and B2O3 (Alfar Aeser, 99.9%). Measurements and characterizations such as density and molar volume measurements, XRD analysis, FTIR, and UV–Vis spectroscopes were performed on the studied glasses. The objective was to determine the glasses’ applicability in optoelectronics, non-linear optics, and laser technologies through polarizability, linear electric susceptibility, and optical basicity study. Apart from confirming the amorphous nature of the glasses, the XRD analysis identified the presence of a crystalline phase of tellurium oxide (α-TeO2) formed. The FTIR spectral study revealed the presence of TeO3, BO3, and SiO4 structural units in the studied glasses. The refractive index (2.3026 – 2.2651), molar polarizability (8.0696 – 9.4334 A3), oxide ion polarizability (3.2970 – 3.6202 A3), electronic polarizability (0.2296 – 0.2335 A3), dielectric constant (5.1307 – 5.3019), optical basicity (0.6719 – 0.7998), metallization criterion (0.410853 – 0.420714) and electric susceptibility (0.3286 – 0.3422 esu) of the glasses were presented. With the high refractive index and favourable electronic/oxide ion polarizability as well as good electric susceptibility, the glasses have shown great potential for optical fibre and laser applications. Metallization criterion value falls in the range of glasses with great potentials for non-linear optical application. The dielectric value suggests the glasses represent wideband semiconducting glasses believed to be good for application in microelectronic substrates fabrication.